Powers and Authorities: Preaching Romans 8:35-39 - Coffman, Kristofer (Word & world, 2019)
A tendency in modern Christianity is to reduce the power of the Gospel of Jesus Christ to moral and ethical teaching. Yet Paul understands that the Christian is faced by powers beyond their control, and that it is God alone who will protect. The Christian preacher does not diminish these powers but reminds hearers of the power of God to overcome all other powers.